The Effectiveness of Digital Marketing: A Case Study of One Bowl Soup MSMEs - Lady, Lady; Delfina, Delfina; Ng, Irvin; Quinn, Fionna; Wijaya, Alexander Janio; Lie, Hardy Winata (Universitas Bunda Mulia, 2023)
Digital marketing is a key factor in facing business competition in the current era. Effective digital marketing strategy implementation could lead MSMEs to maximize the market potential available in social media. Therefore, this research is conducted to investigate the effectiveness of digital marketing implemented for One Bowl Soup. As previous research doesn’t show an actual comparison regarding before and after the suggested strategy implemented, this research does not only overcome the referred limitation, but is not limited to only 2 social medias and comprised of major social medias which has highest active users in Indonesia simultaneously. A qualitative approach is utilized, and customers of One Bowl Soup are collected as samples for this research. It was found that social media usage by enterprises, including MSMEs, would improve the brand awareness of residents towards said enterprise. Moreover, for Instagram, which majority of interviewed sample uses Instagram in their daily life, including searching about local culinary options. After using social media, One Bowl Soup has improved visibility or brand awareness in Batam City, Indonesia, which can be seen from profile traffic insights provided by each social media.